Phosphate Control and 25-Hydroxycholecalciferol Administration in Preventing Experimental Renal Osteodystrophy in the Dog - Rutherford, W. E. (1977)
Previous studies from this laboratory demonstrated that secondary hyperparathyroidism in dogs with chronic renal disease may occur, at least in part, as a consequence of the need for progressive adaptation in renal phosphorus (P) excretion that occurs as glomerular filtration rate falls. However, the studies were of relatively short duration. Moreover, no information emerged regarding a potential role of calcium malabsorption in the pathogenesis of secondary hyperparathyroidism. The short duration of the protocol did not lend itself to the study of the effect of P control or the administration of vitamin D in the pathogenesis of renal osteodystrophy. In the present studies, 14 dogs with experimental chronic renal disease were studied serially for a period of 2 yr. Each animal was studied first with two normal kidneys on an intake of P of 1,200 mg/day. Then, renal insufficiency was produced by 5/6 nephrectomy. The dogs then were divided into three groups. In group I, 1,200 mg/day P intake was administered for the full 2 yr. In group II, P intake was reduced from the initial 1,200 mg/day, in proportion to the measured fall in glomerular filtration rate, in an effort to obviate the renal adaptation in P excretion. In group III, “proportional reduction” of P intake also was employed; but in addition, 20 μg of 25(OH)D(3) were administered orally three times a week. In group I, parathyroid hormone (PTH) levels rose throughout the 2-yr period reaching a final concentration of 557±70 U (normal 10-60). In group II, values for PTH remained normal throughout the 1st yr, increased modestly between the 12th and the 18th mo, but then did not rise after the 18th mo. In group III, no elevation of PTH levels was observed at any time; however, these animals were hypercalcemic. Histomorphologic analyses of the ribs of these dogs were performed serially throughout the 2-yr period. A linear relationship was obtained between the osteoclastic resorption surface and the concentration of circulating immunoreactive PTH. The osteoid volume was greater in group I animals when compared to those in group II. None of the morphologic abnormalities associated with renal osteodystrophy were observed in the animals in the third group.